Comparative Analysis Of Employee Work Stress Based On Work Shifts At Pt. Pelita Adi Pratama Tanjung Balai City - Lubis, salsabila; Harahap, Reni Agustina (Journal for Quality in Public Health, 2023)
Work stress is a consequence of every action taken by employees in dealing with work, where the situation places employees on physical and psychological demands that can interfere with work productivity and the stability of daily life, one of the causes of work stress is work shifts The aim of this research is to find out the comparison of work stress for employees who enter the morning shift and night shift employees. When this research was conducted from February 2023 to June 2023. This study used a quantitative survey method with a cross-sectional design. The sampling technique used purposive sampling because the researchers chose samples based on working hours, namely morning and evening shift employees with a total sample of 60 employees, namely 30 morning shift employees and 30 night shift employees. Data collection included filling in the prepared questionnaire, namely the Occupational Stress Inventory-Revised EditionTM (OSI-RTM) questionnaire with closed questions consisting of 28 items. All data were analyzed using SPSS using an independent sample t-test. The results showed that there were differences in work stress for morning shift employees and night shift employees with a value (sig = 0.000). Based on this research, it is hoped that it can be an improvement for the company regarding employee comfort by making additional work shifts to 3 shifts within 8 hours/shift with different employees.